Identifikasi Makanan Halal dalam Perspektif Hifz al-Nasl pada UMKM Tahu Agung Jaya Bangkalan Madura - Alim, Rohmat Badri; Rohman, Abdur; Dzikrulloh, Dzikrulloh (Jurnal Riset Agama, 2023)
Food is a basic need for humankind. A Muslim must pay attention to the halalness of the food he consumes. The command to consume halal food has been conveyed clearly by Allah SWT in the Qur'an and this can be understood in the concept of maqasid sharia. Maqasid sharia in halal food is the benefit behind consuming halal food as prescribed by religion. This research aims to understand the Identification of Halal Food Products from the Hifz al Nasl Perspective in UMKM Tahu Agung Jaya Bangkalan Madura. This research uses a qualitative method, namely a descriptive approach and this type of research is field research. Researchers conducted observations, interviews and documentation to obtain primary and secondary data. This research provides results that in the perspective of hifz al nasl it includes three needs, namely primary (dharuriyyah), secondary (hajiyyat), and tertiary (tahsiniyyat). The primary need (dharuriyyah), namely the selection of soybean raw materials used, must continue to be paid attention to. Secondary needs (hajiyyat) are field surveys to see and buy selected and quality soybeans. The tertiary requirement (tahsiniyyat) is that the tools used in producing tofu must always be clean.